An acoustic approach to determine tip vortex cavitation inception for an elliptical hydrofoil considering nuclei-seeding. (April 2017) - Song, Mingtai; Xu, Lianghao; Peng, Xiaoxing; Tang, Denghai
Highlights: We propose an acoustic criterion to determine tip vortex cavitation inception. The acoustic criterion is applicable to both non-nuclei-seeding and nuclei-seeding. Trend between sound pressure level and cavitation number shows an inverse N-shape. The reason is attributed to the variable pressure difference and vortex roll-up. We confirm the key role nuclei distribution plays in cavitation inception process. Abstract: Tip vortex cavitation is usually the first type of propeller cavitation to appear with intense noise. The precise prediction of tip vortex cavitation inception is of great importance. In this paper, via an acoustic approach an experimental investigation on tip vortex cavitation inception for an elliptical hydrofoil has been done in a cavitation mechanism tunnel. For non-nuclei-seeding conditions, the sound level "collapses" when the tip vortex cavitation approaches desinence and there exists an inverse N-shape curve between the sound pressure level and cavitation number, drastically different from the generally known S-shape curve. Three nuclei-seeding conditions are then investigated to study the nuclei effects on the tip vortex cavitation inception. We propose an acoustic criterion to determine tip vortex cavitation inception applicable to both non-nuclei-seeding and nuclei-seeding conditions. The results confirm that the nuclei content and distribution in water indeed play an important role in the cavitation inception process. Supplemental observations from the high-speed video camera validate the proposed acoustic method.